Seasonal and interannual variability of fish species composition in catches of bottom nets in the Russian waters of the Kunashir Strait - A. Ya. Velikanov; I. N. Mukhametov; G. V. Shevchenko; Zh. R. Tshai; V. N. Chastikov (Известия ТИНРО, 2023)
Seasonal and interannual variability of the demersal fish species composition is considered for the depths of 70–315 m in the eastern Kunashir Strait on the data obtained in 1998–2014. The fish community includes the species belonged to nine zoogeographical complexes and eighth ecological groups. Among them, species diversity is higher for the arctic-boreal, wide-boreal Pacific, wide-boreal Asian, and low-boreal Asian complexes and for the sublittoral, elittoral, and mesobental groups. The species diversity of fish in the surveyed area depends on seasonal migrations of demersal and pelagic fishes, including pacific salmon and some subtropical and tropical species. Interannual variations in the species composition are determined mainly by changes in the depth of netting and water temperature, but do not depend on the timing of samples collection during a season.